Mitigating droughts and floods in agriculture. Policy lessons and approaches - (:unkn) unknown (My University, 2016)
Der Landwirtschaft im 21. Jahrhundert machen extreme Wetterereignisse zu schaffen, die aufgrund des Klimawandels immer häufiger vorkommen und auch in ihrer Intensität zugenommen haben. Der Bericht analysiert die politischen Ansätze, wie man in der Landwirtschaft mit Dürren und Überschwemmungen umgehen kann. Er gibt zudem Empfehlungen in den Bereichen Wasserrechte und -verteilung, Zugang zu meteorologischen und hydrologischen Informationen, Innovation und Bildung sowie Versicherungs- und Entschädigungsregelungen.

Climate change is expected to increase the frequency and magnitude of extreme weather events, notably of droughts and floods to which the agriculture sector is particularly exposed. While agricultural productivity growth and policy development have allowed to better cope with these risks and reduce overall impacts on the sector and commodity markets, there is substantial room to improve policy responses and co-ordinate across policy domains, including with respect to water rights and allocation, weather and hydrological information, innovation and education, and insurance and compensation schemes. Indeed, drought and flood risks are likely to become a major policy concern as increasing population will increase the demand for food, feed, fibre, and energy, not to mention the competition for water resources, and urbanisation will increase the demand for flood protection and mitigation, raising the issue of the allocation of flood risks across sectors and areas.
Keywords: Landwirtschaft; Überschwemmung; Dürre; Klima; Wasserrecht; Wasserverteilung; Agrarpolitik; Umweltpolitik; Wassermanagement; Klimawandel